Exploring the roles of genes associated with leukocyte transendothelial migration in liver cirrhosis development - Lei Feng; Jiao He; YanLing Mu; Jie Liu; Yong Yao (PLoS ONE, 2026)
Background Individuals with liver cirrhosis (LC) have an exceptionally high mortality rate. We aim to discover new biomarkers or new therapeutic targets for LC early diagnosis and treatment. Methods The human LC microarray datasets were obtained from the NCBI-GEO database. Firstly, differentially expressed analysis and WGCNA were performed to detect LC key genes. Protein-protein interaction (PPI) hubs revealed new regulatory mechanisms for LC-related genes. Functional enrichment and immune infiltration analyses were employed to reveal underlying mechanisms of LC progression. Then, key genes were further screened for constructing diagnostic nomogram for LC and predicting the prognosis of LC. CB-Dock-2 was employed to explore potential therapeutic agents for LC based on the identified key genes.Finally, immunohistochemistry was performed to detect the expression levels of the key genes in liver tissues from patients with liver cirrhosis and healthy controls. Results The integrated LC dataset identified 749 LC key genes by intersecting WGCNA and differential expression analyses. PPI analysis identified 15 genes as key regulators in LC development, predominantly enriched in inflammatory and immune regulatory pathways. We conducted an in-depth analysis of two leukocyte transendothelial migration (LTM)-associated genes (MMP2 and ITGB2) among these 15 hub genes, revealing their involvement in the construction of the immune microenvironment in LC. A nomogram based on MMP2 and ITGB2 had favorable diagnostic performance for LC, and ITGB2 showed potential in predicting LC prognosis. Through molecular docking approaches, this study further identified several antioxidant and anti-inflammatory agents with therapeutic potential for LC. Immunohistochemical staining revealed significantly elevated protein levels of MMP2 and ITGB2 in liver tissues from cirrhotic patients compared to healthy controls. Conclusions LTM-associated genes, namely MMP2 and ITGB2, are associated with LC and may represent candidate biomarkers or potential targets requiring further experimental validation.